CREATING WEALTH. INNOVATE AND ENJOY - Peña, Viviana H. (2020)
The comment of this book, points out the friendly way of telling the story of a successful company used by the author. The story of this company shows that success is possible when a person prepares itself in order to make its dream comes true. The company started during the difficult times for Peruvian national economy but the application of good business practices allowed it to reinvent itself and adapt in order to face different situations it has gone through. This case evidence what can be achieved when professional maturity, good business practices, passion and a great deal of personal sacrifice are combined.